STRENGTHENING ISLAMIC BANKING LITERACY THROUGH MUDHARABAH PRODUCTS AND CONTRACTS AMONG TEACHERS AT ISLAMIC SCHOOLS AND ISLAMIC BOARDING SCHOOLS IN MARON VILLAGE, SRENGAT DISTRICT, BLITAR REGENCY - Muhamad Aqim Adlan; Labib Muzaki Shobir; Sri Wigati; Deris Lazuardi (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This community service activity aims to align the reasoning of fiqh muamalah with the technical aspects of Islamic banking through a paradigm shift among teachers at Madrasah Diniyah and Islamic boarding schools in Maron Village, Blitar, as the primary target, using the Service Learning method integrated with the Experiential Learning model, to enhance literacy in Islamic financial products as a preventive measure against non-Islamic financial practices among religious educators. The method employed is a qualitative approach using the Service Learning method integrated through the Experiential Learning model. The sample was determined using purposive sampling, involving 20 teachers at the Al-Hikmah Foundation. The results of this community service project indicate that the integration of Service Learning and Experiential Learning effectively enriches understanding of the theoretical aspects of classical Islamic texts, leading to the practical application of banking products and contracts that are adaptable to current realities. Experience-based learning through realistic contract simulations has proven capable of building administrative trust and enhancing Islamic financial inclusion within the pesantren environment. The synergy between fiqh reasoning and banking techniques has resulted in a collaborative initiative for self-reliant capital based on mudharabah contracts as a preventive measure against non-Islamic financial practices, aimed at supporting the welfare of society and the sustainable economic independence of the Muslim community in Indonesia.